Hematite iron oxide nano-particles: facile synthesis and their chemi-resistive response towards hydrogen. (30th April 2015) - Atyam, K K; Ghosh, A; Mukherjee, K; Majumder, S B
Abstract: In the present work, hematite iron oxide nano-particles are synthesized through a facile wet chemical precipitation route. The phase formation behavior and microstructure evolution of the synthesized nano-particles are studied using infrared spectroscopy in conjunction with x-ray diffraction analyses and electron microscopy. Chemi-resistive type hydrogen sensing characteristics (e.g. response %, response time, recovery time) of hematite iron oxide nano-particulate sensing element are evaluated using an automated, dynamic flow gas sensing measurement set-up. The sensing characteristics are measured by varying the operating temperature (275–350 °C) of the sensor and concentration of hydrogen (250–1660 ppm). From the operating temperature dependence of response and recovery times, we have estimated the respective activation energies for response and recovery processes.